Analisis Evaluasi Usability Web Akademik Fakultas Teknik Unsika dengan Model UWIS - Herwanto, Dene; Hadining, Aulia Fashanah; Puspasari, Rianita (Universitas Suryakancana, 2018)
Abstractâ€” Utilization of information and communication technology (ICT) in education becomes an absolute thing to do, in order to improve the quality of education, service effectiveness and become a strength for higher education institutions. One application of aspects of ICT in college is academic web. In the Faculty of Engineering University Singaperbangsa Karawang, academic information system is known by the web SIAKAD (Academic Information System) Faculty of Engineering Unsika. Web SIAKAD FT Unsika aims to manage data and facilitate the integration associated with academic information, but on its application may occur mismatch between procedures established in the web with its implementation. Therefore, please note the behavior of SIAKAD web users, also conducted testing of the academic web interface. This is considering that the web SIAKAD FT Unsika is still in development stage.Â Stages in this study started from a preliminary study of the use of the web SIAKAD and continued with research on the usability of the web SIAKAD. From the results of the study note that there are five dimensions that affect web usability SIAKAD FT Unsika that must be repaired by the web developers, namely Responsiveness (RS), Web design (WD), Assurance (A), Readability (RD), and Navigation (N).Keywordsâ€” academic web; usability; university